Understanding inclusive STEM high schools as opportunity structures for underrepresented students: Critical components. Issue 5 (29th December 2017) - Lynch, Sharon J.; Burton, Erin Peters; Behrend, Tara; House, Ann; Ford, Michael; Spillane, Nancy; Matray, Shari; Han, Edmund; Means, Barbara
Abstract: Inclusive STEM high schools (ISHSs) can be viewed as opportunity structures for students underrepresented in STEM. By opportunity structures, we mean an education that provides not only access to high quality STEM curriculum and instruction or "opportunity to learn, " but also the capacity to create learning environments where students can build STEM social capital and the dispositions, knowledge, skills, and networks to be successful in STEM college majors and careers. This is a cross‐case analysis of case studies that describe the design and implementation of eight "exemplar" ISHSs. Beginning with 10 hypothesized critical components, we found evidence for all 10, but present in unique patterns of prominence, depending on the school context. Further inductive analysis located an additional four emergent critical components that complete the picture of how these successful ISHSs were able to achieve their goals. Importantly, across schools, four components stood out as foundational: a flexible and autonomous administrative structure; a college‐preparatory, STEM‐focused curriculum for all; well‐prepared STEM teachers and professionalized teaching staffs; and supports for students in underrepresented groups. Although many of the critical components found in the ISHSs are also found in the school reform literature, these schools also had characteristics unique to STEM education. This paper is important in understanding STEM high schools as opportunity structures and as a school reform alternative that can help solve equity and social mobility gaps in STEM.